History of Music Therapy in Thailand - Trakarnrung, Somchai (Journal of the Faculty of Arts, Silpakorn University, 2021)
The objective of this article is to study the history of music therapy in Thailand focusing on three areas: (1) Music Therapy Clinic, (2) Music Therapy Education, and (3) Music Therapy Research. The research methodology used includes semi-structured interviews with three different professionals including music therapists and a medical doctor, followed by analyzing documented evidence such as books, text books, research articles, research reports, and academic articles. The results show that Thailand began to offer music therapy in 1990. The music interventions used were recreational music activities, playing musical instruments, singing and movement. In the education field, Thailand has offered two types of education training including degree-program and short-course training since 2007. As to the history of music therapy, the results indicate that music therapy research in Thailand has been continuously conducted since 1985. The benefit of this study is to provide further background of music therapy history in Thailand to be used as academic database for music therapists, as well as to further the study of this subject.